Microneurography as a tool to develop decoding algorithms for peripheral neuro-controlled hand prostheses. - Petrini, Francesco M.; Mazzoni, Alberto; Rigosa, Jacopo; Giambattistelli, Federica; Granata, Giuseppe; Barra, Beatrice; Pampaloni, Alessandra; Guglielmelli, Eugenio; Zollo, Loredana; Capogrosso, Marco; Micera, Silvestro; Raspopovic, Stanisa (BioMedical Engineering OnLine, 2019)
Background: The usability of dexterous hand prostheses is still hampered by the lack of natural and effective control strategies. A decoding strategy based on the processing of descending efferent neural signals recorded using peripheral neural interfaces could be a solution to such limitation. Unfortunately, this choice is still restrained by the reduced knowledge of the dynamics of human efferent signals recorded from the nerves and associated to hand movements.Findings: To address this issue, in this work we acquired neural efferent activities from healthy subjects performing hand-related tasks using ultrasound-guided microneurography, a minimally invasive technique, which employs needles, inserted percutaneously, to record from nerve fibers. These signals allowed us to identify neural features correlated with force and velocity of finger movements that were used to decode motor intentions. We developed computational models, which confirmed the potential translatability of these results showing how these neural features hold in absence of feedback and when implantable intrafascicular recording, rather than microneurography, is performed.Conclusions: Our results are a proof of principle that microneurography could be used as a useful tool to assist the development of more effective hand prostheses.